2000
DOI: 10.1002/(sici)1097-0290(19960820)51:4<458::aid-bit9>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high shear on proteins

Abstract: Shear is present in almost all bioprocesses and high shear is associated with processes involving agitation and emulsification. The purpose of this study is to investigate the effect of high shear and high shear rate on proteins. Two concentric cylinder‐based shear systems were used. One was a closed concentric‐cylinder shear device (CCSD) and the other was a homogenizer with a rotor/stator assembly. Mathematical modeling of these systems allowed calculation of the shear rate and shear. The CCSD generated low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 17 publications
2
88
1
Order By: Relevance
“…Thus, it is highly probable that the PEG chains conjugated onto the surface of ADV physically protected the viral surface coat proteins from being denatured and aggregated upon exposure to the water/ oil interface under high shear stress conditions. The amount of soluble ADV fraction did not continuously decrease with increasing homogenization time, suggesting that ADV was mainly aggregated and precipitated by exposure to the interface between the water and oil phases during the homogenization process (29). Thus, the extent of viral aggregation may be saturated even after prolonged homoge- nization due to the limited interfacial area in the water/oil emulsion solution.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is highly probable that the PEG chains conjugated onto the surface of ADV physically protected the viral surface coat proteins from being denatured and aggregated upon exposure to the water/ oil interface under high shear stress conditions. The amount of soluble ADV fraction did not continuously decrease with increasing homogenization time, suggesting that ADV was mainly aggregated and precipitated by exposure to the interface between the water and oil phases during the homogenization process (29). Thus, the extent of viral aggregation may be saturated even after prolonged homoge- nization due to the limited interfacial area in the water/oil emulsion solution.…”
Section: Resultsmentioning
confidence: 99%
“…After initial adsorption of the protein, surface tension forces at various interfaces (i.e., air-liquid interface, solid-liquid interface) can drive aggregation by affecting structural integrity of protein molecules that populate the interfacial region (142,337,341,342). Structural perturbation at the surface combining with desorption of partially unfolded proteins from the surface can lead to nucleation and growth of aggregates in the bulk solution (142,(343)(344)(345)(346).…”
Section: Surface Adsorptionmentioning
confidence: 99%
“…For example, previous studies on the effects of both high shear ([10 7 ) and high shear rate ([10 5 s 21 ), using concentric cylinder-based systems, on recombinant human growth hormone (rhGH) ($22 kDa) and recombinant human deoxyribonuclease (rhDNase) ($31 kDa) showed that rhDNase was more resistant to shear-effects. 38 For instance, whereas scanning microcalorimetry and SDS-PAGE analysis of extensively sheared solutions showed changes in the melting temperature of rhGH and the presence of low molecular weight fragments, respectively, no such changes were observed for rhDNase. Interestingly, the observed structural changes in rhGH were not detected in both the near and the far-UV circular dichroism spectral profile of the sample.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%
“…Interestingly, the observed structural changes in rhGH were not detected in both the near and the far-UV circular dichroism spectral profile of the sample. 38 Further studies on both samples showed that rhGH denatured upon exposure to high shear in the presence of an air-liquid interface whereas rhDNase remained relatively stable. 64 The stability of rhDNase was attributed to its comparatively high surface tension and low foaming tendency in solution.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%